Dramaturgy of Ustadh Abi Azkakia's da'wah in the Mobile Legends game - Arini Fahma Qona'ati; Dicky Nur Rahman; Eta Husniya; Sokhi Huda (Islamic Communication Journal, 2023)
Da'wah strategy innovation is needed in the midst of various challenges. This paper examines the phenomenon of preaching by Ustadh Abi Azkakia (preacher) in the perspective of Erving Goffman's dramaturgical theory. The Ustadh carried out da'wah through the Mobile Legends game in a unique way of preaching. This study uses a textual qualitative research analysis method with a case study type. The results of this study indicate that the preacher conveys his da'wah message through the Mobile Legends game interspersed with jokes and attracts many young fans called the Assembly of Nurul Legends gaming congregation. The average Mobile Legends gamer says harshly, with this preaching it makes these words good words. The preacher shows himself as an example from the way he interacts with his missionary partners, the way he talks, dresses politely, to a simple way of life. This research contributes to the development of da'wah dramaturgy studies, but this research has limited data which is only analyzed based on literature data. ***Inovasi strategi dalam berdakwah sangat diperlukan di tengah berbagai tantangan. Tulisan ini mengkaji tentang fenomena dakwah Ustadh Abi Azkakia (pendakwah) dalam perspektif teori dramaturgi Erving Goffman. Ustadh tersebut melakukan dakwah melalui permainan Mobile Legends dengan cara dakwah yang unik. Penelitian ini menggunakan metode analisis penelitian kualitatif tekstual dengan jenis studi kasus. Hasil studi ini menunjukkan bahwa pendakwah menyampaikan pesan dakwahnya melalui permainan Mobile Legends dengan diselingi candaan dan menarik banyak penggemar muda yang bernama jamaah gaming Majelis Nurul Legends. Rata-rata gamers Mobile Legends berkata kasar, dengan adanya dakwah ini membuat perkataan tersebut menjadi perkataan yang baik. Pendakwah menunjukkan dirinya sebagai teladan dari caranya berinteraksi dengan mitra dakwah, cara-cara berbicara, berpakaian yang sopan, hingga cara hidup yang sederhana. Penelitian ini berkontribusi dalam memberikan pengembangan kajian dramaturgi dakwah, namun penelitian ini memiliki keterbatasan data yang hanya dianalisis berdasarkan data literatur.